Evaluation of the effectiveness of adjuvant anti-progestogen therapy after conservative myomectomy in women of reproductive age - Yanina A Lebedeva; Inna I Kovalenko; Oleg L Molchanov; Dmitrii V Baibuz; Natalia V Kulikova (IP Berlin A.V., 2019)
Relevance. Due to the high prevalence of uterine fibroids in young women and the possible effect on reproductive potential, the development, implementation and application of the most benign treatment methods are a priority. Aim. To evaluate the effectiveness of adjuvant anti-progestogen therapy after conservative myomectomy in women of reproductive age. Materials and methods. A comparative analysis of the results of treatment of patients of reproductive age with uterine myoma has been carried out. Group 1 (n=38) included patients who underwent conservative myomectomy and/or hysteroresectoscopy without subsequent anti-relapse drug therapy. The average age is 31.5 years (4.6). Group 2 (n=43) included patients after conservative myomectomy who received mifepristone as anti-relapse therapy after surgery. The average age is 31.9 years (4.5). Results. Mifepristone therapy, as an adjuvant treatment after conservative myomectomy, can significantly reduce the risk of recurrence, stabilize the size of the uterus, reduce the severity of clinical manifestations in the form of pain syndrome and heavy menstruation associated with relapse, thereby improving the reproductive health of women. Conclusions. The use of adjuvant anti-progestogen therapy after conservative myomectomy in women of reproductive age is a very effective method for treating uterine fibroids and can be considered as a therapy of choice in such patients.